JoJo's guide to making your own fun #doityourself - Siwa, JoJo (London Puffin, 2018)
JoJo Siwa offers fans her best, most engaging book ever-jam-packed with inspiration for every day. Formatted as a back-to-school book with a year's worth of activities for rainy days, birthday parties, days at the beach, and everything in between, this interactive book will provide dozens of ideas to jump-start the creative brain. Making slime, crafting the best friendship bracelets, and planning a mother-daughter spa day at home are just a few things JoJo loves-and wants you to enjoy, too
Arts
2
Keywords: Amusements; Siwa, JoJo -- 2003 -- Juvenile literature